Credibilistic Location‐Routing Model for Hazardous Materials Transportation. Issue 1 (29th September 2014) - Wei, Meiyi; Yu, Lean; Li, Xiang; Yang, Lixing; Li, Xiang; Ralescu, Dan A.
<x xml:space="preserve">Abstract</x> With the development of social economy, the increasing demand on hazardous materials transportation has received considerable attention around the world and the location‐routing problem has become a hot topic of study. The goal of our work is to obtain the best balance between the transportation risk and cost under the assumptions that the transportation costs and the number of affected people are fuzzy variables. Within the framework of credibility theory, we propose a chance‐constrained programming model and design a fuzzy simulation–based genetic algorithm to solve the model. Numerical experiments are given to illustrate the efficiency of the proposed model and algorithm.